Look back in anger - Osborne, John; Prasad,G.J.V. (Delhi : Faber and Faber, 2006)
Asolo Theater Festival, the state theater, 1968 winter season. The Asolo Theater Festival production company, the acting company and playbill for the winter season including "Henry Fourth, Part 1," Shakespeare, "Servant of Two Masters," Goldini, "Tartuffe," Moliere, "J.B.," MacLeish and "Look Back in Anger," Osborne. "Look Back in Anger," by John Osborne, directed by Paul R. Weidner, senery by Ray Perry, costumes by Joy Breckenridge, lighting by Richard C. Evans, original music by Stephen Smith.
Includes bibliography
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: English Drama; Souvenir programs -- Florida -- Sarasota; Theater programs -- Florida -- Sarasota; Souvenir programs -- 1968.; Theater programs -- 1968.